1983
DOI: 10.1126/science.6297001
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene from Human EJ Bladder Carcinoma Is Located on the Short Arm of Chromosome 11

Abstract: The human cellular homolog of the transforming DNA sequence isolated from the bladder carcinoma cell line EJ was localized on the short arm of human chromosome 11 by Southern blot analysis of human-rodent hybrid cell DNA. This locus contains human sequences homologous to the Harvey murine sarcoma virus v-Ha-ras oncogene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…To identify this activating gene, binding activity was measured in several hamster-human hybrid cell lines (13,14,28,31) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…To identify this activating gene, binding activity was measured in several hamster-human hybrid cell lines (13,14,28,31) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…The two genes therefore occur on different chromosomes in both mice and humans. In contrast, the Ha-ras-1 oncogene cosegregates with int-2 on mouse chromosome 7 (20,32) and human chromosome 11 (5), albeit relatively distant from one another (llplS and 11q13, respectively) (5,18,35). Neither gene is particularly close to the deletion involved in Wilms' tumor (18), but the identification of a series of fairly common RFLPs, detailed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes such as the human 83-globin gene cluster (HBBC), the parathyroid hormone (PTH) gene, the oncogene HRASI (formerly termed c-Ha-ras-1), and the insulin gene have been assigned to the short arm of chromosome 11 (1)(2)(3)(4)(5). By using DNA polymorphisms for linkage analysis, it has been shown that PTH, HBBC, HRASI, and the insulin gene are closely linked to each other (6,7).…”
mentioning
confidence: 99%